Analysis Design of E-IM3 Information System with Object Oriented Design - Sri Anardani; Puguh Jayadi; Wasilatul Murtafiah; Rischa Pramudia Trisnani (International journal of technology and education research, 2025)
This research aims to analyse and design an information system based on the E-IM3 model using the Object-Oriented Design (OOD) approach to support the digital learning and decision-making process, especially for students with slow learning needs. The E-IM3 model, which consists of the stages of Identifying Problems, Building Ideas, Clarifying Ideas, and Assessing the Feasibility of Ideas, serves as a foundation to foster students' critical and reflective thinking. In Indonesian, E-IM3 is electronic based Identifikasi masalah, Membangun ide, Mengklarifikasi ide, dan Menilai kewajaran ide. Utilizing the System Development Life Cycle (SDLC), this research applies Object Oriented Analysis (OOA) and OOD to translate pedagogical needs into a technically robust system. The system design involves UML modelling elements starting from activity diagrams to user interfaces. Each component of the system was organized into boundary, control, and entity classes, reflecting a modular, maintainable, and user-cantered design. The user interface was developed to be intuitive and inclusive, facilitating gradual student engagement in decision-making tasks. The results show that the E-IM3 based system effectively supports personalized learning pathways and encourages high-level cognitive engagement through technology integration. This research contributes to the development of adaptive educational technologies aligned with technical and pedagogical standards in the digital age.